2019
DOI: 10.34088/kojose.535175
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization of Some Foil Alloys Based on Nickel

Abstract: In this research, we carried out some structural and magnetic analyses of foil alloys in the form of NixCuyFez (x=0.65, y=0.33, z=0.02); NixFeyCuzMot (x=0.77, y=0.14, z=0.05, t=0.04); NixCryCoz(MoTiAlFe)t (x=0. 58, y=0.19, z=0.14, t=0.09) and NixCoyCrzFet(NMoMn)w (x=0.13, y=0.425, z=0.20, t=0.20, w=0.045). In order to have knowledge about the magnetic properties, we use electron paramagnetic resonance spectroscopy which is effective to see the paramagnetism in the structure. For structural analyses, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Many studies about alloys for different purposes were reported before [6][7][8][9][10][11][12][13][14]. Among the alloys, Ni-based alloys, Inconel-617 and Incoloy-800HT, were also studied by many researchers previously [1,4,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies about alloys for different purposes were reported before [6][7][8][9][10][11][12][13][14]. Among the alloys, Ni-based alloys, Inconel-617 and Incoloy-800HT, were also studied by many researchers previously [1,4,[15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%